A p-Si/NiCoSex core/shell nanopillar array photocathode for enhanced photoelectrochemical hydrogen production. Issue 10 (19th September 2016) - Zhang, Hongxiu; Ding, Qi; He, Denghong; Liu, Hu; Liu, Wei; Li, Zhongjian; Yang, Bin; Zhang, Xingwang; Lei, Lecheng; Jin, Song
Abstract : We report the rational design and successful preparation of p-Si/NiCoSe x core/shell nanopillar array photocathodes for enhanced solar-driven photoelectrochemical hydrogen generation. Abstract : Three-dimensional (3D) semiconductor photoelectrodes are promising for improving the efficiency of photoelectrochemical (PEC) water splitting for hydrogen generation, but a high-quality heterojunction between the semiconductor and the carefully selected high-performance electrocatalyst is crucial. Here, we report the rational design of a novel 3D p-Si/NiCoSe x core/shell nanopillar (NP) array photocathode via uniform photo-assisted electrodeposition of NiCoSe x electrocatalyst on bamboo shoot-like Si NP array backbones. We demonstrate its enhanced PEC performance with a photocurrent density of −37.5 mA cm −2 at 0 V ( vs. RHE) under simulated 100 mW cm −2 (1 Sun) irradiation with an AM 1.5 G filter, which is the highest value reported for p-type Si photocathodes. The synergistic effects of the excellent light harvesting of the Si NP array core and the good optical transparency, as well as the excellent electrocatalytic activity of the NiCoSe x shell, boost the production and utilization of photogenerated electrons. The design of p-Si/NiCoSe x core/shell NP arrays offers a new strategy for preparing highly efficient photoelectrochemical solar energy conversion devices.